Sentinel Surveillance for HIV Among People who Inject Drugs, Gia Lai Province, Vietnam - Hoang, Thang Nghia; Pham, Duoc Tho; Nguyen, Ha Thi Thu (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: HIV remains a public health challenge, especially among people who inject drug (PWID). The HIV Sentinel Surveillance (HSS), together with the HIV/AIDS case reporting, are two core components of the HIV/AIDS surveillance system providing systematic, on-going monitoring of HIV epidemic in Viet Nam. The HSS was first conducted in 1994 to determine HIV prevalence among the high-risk group by collecting blood sample. But in 2009, this system was monitored the risk behaviors by addition of a brief behavioral questionnaire, known as HSS+. In Central Highland, the HIV situation in Gia Lai province has primarily affected PWID, which are main criteria to select into the surveillance system.Aims: This study aims to determine risk factors for HIV infection to improve intervention programs for PWID in Gia Lai province, Vietnam.Methods: We performed a cross-sectional survey of 150 randomly selected PWID from June to September 2014 in Gia Lai province. Face-to-face interviews were conducted to collect information regarding drug use, sexual behavior, accessibility of HIV/AIDS counseling and testing services. Blood samples were collected and tested for the presence of HIV antibodies using ELISA and rapid test. For data analysis, the frequencies and proportions were calculated. Chi-square or Fisher’s exact tests and multivariable logistic regression were performed to assess the association between risk factors and HIV infection.Results: We identified 14 infections among 150 PWID (prevalence = 9.3%). Among PWID, 22.7% (34/150) had shared needles and 3 HIV prevalence among PWIDs injecting drug for at least 3 years was 2.4%. HIV prevalence among PWIDs who have had sexual intercourse with more than one commercial sex worker (CSW) per month was 6.5%. In multivariable logistic regression, the odds of HIV infection with sharing needles, injecting for over 3 years, and sexual intercourse with more than one CSW per month was 6.7 (95% CI: 1.6-27.7), 6.1 (95% CI: 1.2-30.3) and with 4.0 (95% CI: 1.0-15.3), respectively.Conclusion: We identified a few modifiable risk factors among PWID. Based on these data, we recommend improving harm reduction intervention and behavior change communication. The sentinel surveillance site should continue monitoring PWID behavior over time.